Quality Attributes and Fatty Acid, Volatile and Sensory Profiles of “Arbequina” hydroSOStainable Olive Oil - Lucía Sánchez-Rodríguez (Molecules, 2019)
The use of deficit irrigation techniques on olive orchards is the main trend aiming to optimize water savings while improving functional and sensory characteristics of oils from trees under deficit irrigation techniques. The brand hydroSOStainable has been defined for crops produced under water restriction conditions. HydroSOStainable olive oils obtained under two new regulated deficit irrigation and one sustained deficit irrigation treatments in “Arbequina” olive trees were evaluated by analyzing quality parameters, antioxidant activity, total phenol content, fatty acid profile, volatile compounds, and sensory descriptors. Results showed that some of these irrigation strategies improved the phenol content at “moderate” stress levels, slightly enriched the fatty acid profile (~3.5% increased oleic acid and simultaneously decreased saturated fatty acids), and increased some key volatile compounds and also several key sensory attributes. Therefore, hydroSOStainable olive oil may be more attractive to consumers as it is environmentally friendly, has a higher content of several bioactive compounds, and has improved sensory characteristics as compared to control (fully irrigated) oils.